PENERAPAN MODEL CONTEXTUAL TEACHING AND LERANING (CTL) PADA MATERI PENCEMARAN LINGKUNGAN UNTUK MENINGKATKAN HASIL BELAJAR SISWA SMP NEGERI 6 SATAP LIKUPANG BARAT - Bawotong, Lola Kristin; Rungkat, Jovialine Albertine; Paat, Meike (Charm Sains: Jurnal Pendidikan Fisika, 2024)
This research aims to improve student learning outcomes at SMP Negeri 6 SATAP West Likupang by using the application of the contextual teaching and learning (CTL) model on environmental pollution material. The subjects of this research were 16 students in class VII of SMP Negeri 6 SATAP West Likupang, consisting of 6 male students and 10 female students. This type of research is classroom action research which consists of four stages, namely: planning, implementation, observation and reflection. Data was collected using observation methods, documentation studies, and tests in each cycle. The research results obtained showed that there was an increase in the completeness value of learning outcomes, namely from the pre-cycle of 31.25% to the first cycle of 85.71%. In cycle I, the teacher teaching observation stage obtained 86.69% (good) and student activity observation 82.69% (good) and these results had reached the success indicator (KKM 75%) so that the classroom action research was stopped, until cycle I. From The research results prove that lessons through the Contextual Teaching and Learning model on environmental pollution material can improve student learning outcomes.